2012
DOI: 10.1371/journal.pone.0039483
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the Drosophila Fused in Sarcoma (FUS) Homologue Causes Deficient Locomotive Behavior and Shortening of Motoneuron Terminal Branches

Abstract: Mutations in the fused in sarcoma/translated in liposarcoma gene (FUS/TLS, FUS) have been identified in sporadic and familial forms of amyotrophic lateral sclerosis (ALS). FUS is an RNA-binding protein that is normally localized in the nucleus, but is mislocalized to the cytoplasm in ALS, and comprises cytoplasmic inclusions in ALS-affected areas. However, it is still unknown whether the neurodegeneration that occurs in ALS is caused by the loss of FUS nuclear function, or by the gain of toxic function due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 61 publications
0
50
0
Order By: Relevance
“…Transgenic mice homozygous for an inactive FUS allele, for example, fail to suckle and die soon after birth (Hicks et al 2000). Knock down of the FUS homologue Caz in Drosophila causes degeneration of motor neurons and abnormal locomotive behavior (Sasayama et al 2012) whereas expression of wild-type or pathogenic mutations of human FUS in Drosophila induces a similarly severe neural impairment (Chen et al 2011). Therefore, the expression level of FUS protein needs to be critically maintained for normal neuronal function.…”
Section: Als and Ftld: When Aggregation Goes Awrymentioning
confidence: 99%
“…Transgenic mice homozygous for an inactive FUS allele, for example, fail to suckle and die soon after birth (Hicks et al 2000). Knock down of the FUS homologue Caz in Drosophila causes degeneration of motor neurons and abnormal locomotive behavior (Sasayama et al 2012) whereas expression of wild-type or pathogenic mutations of human FUS in Drosophila induces a similarly severe neural impairment (Chen et al 2011). Therefore, the expression level of FUS protein needs to be critically maintained for normal neuronal function.…”
Section: Als and Ftld: When Aggregation Goes Awrymentioning
confidence: 99%
“…Pan-neuronal expression of dFUS RNAi does not affect adult lifespan, but does inhibit climbing. RNAi knockdown in motor neurons also reduces bouton number and length of synaptic branches at the NMJ (Sasayama et al, 2012). Additionally, knockdown in fly eyes causes external degeneration (Azuma et al, 2014;Shimamura et al, 2014).…”
Section: 0 Drosophila Models Of Alsmentioning
confidence: 99%
“…Investigations in some Drosophila , C. elegans and rat models showed that expression of ALS-associated FUS mutants can lead to motor neuron dysfunction and neurodegeneration [15][17]. However, some Drosophila and zebrafish models support that the loss of FUS function can lead to behavioral and structural defects of motor neurons [18], [19]. Exactly how the loss of FUS nuclear function and/or the gain of cytoplasmic cytotoxicity contribute to neurodegeneration at the molecular level is still unknown.…”
Section: Introductionmentioning
confidence: 99%